The Study of Iron Metal (Fe) Content in Water Morning Glory Plants (Ipomoea Aquatica Forsk) using Atomic Absorption Spectrophotometry (AAS) Method - Khusnul Kholifah; Andi Fadllan; Wenty Dwi Yuniarti (Faculty of Science and Technology, Universitas Islam Negeri Walisongo Semarang, 2015)
There are several hazardous material compounds in water morning glory that cannot be consumed. This study aimed to Fe content in water morning glory taken from different locations using Atomic Absorption Spectrophotometry (AAS) method. The data were acquired through documentation method, observational method and experimental method. All of the data were analysed by quantitative approach and descriptive analysis. The number of samples taken was 3 pieces of water morning glory per location. From the AAS method, the results showed that Fe concentrations in all samples varied. The average of Fe content in water taken from Industrial area was 0,258 ppm, from green house was 0 ppm, and from rural area was 0,175 ppm. The numbers of Fe content in water morning glory taken from industrial area were 10,78 ppm, 9,0 ppm, 9,3 ppm; from green house were 1,9 ppm, 4,4 ppm, 2,4 ppm; and from rural area were 6,4 ppm, 4,94 ppm, 4,98 ppm. The results of the study showed that Fe content in water or water morning glory taken from green house and rural area was below the threshold level of metal contamination, meanwhile in industrial area, the Fe content was almost approaching the threshold level of metal contamination. In the industrial area, the water morning glory could be used to reduce water pollution, not as food sources because of the high content of Fe. Meanwhile, in green house and rural area, water morning glory might be consumed by people because of the low content of Fe. © 2015 JNSMR UIN Walisongo. All rights reserved.